Anais Do Simpósio Brasileiro De Computação Ubíqua E Pervasiva (SBCUP) 2018
DOI: 10.5753/sbcup.2018.3291
|View full text |Cite
|
Sign up to set email alerts
|

Construção do Estado da Arte em Estratégias Híbridas para Raciocínio de Contexto: uma Abordagem explorando Revisão Sistemática da Literatura

Abstract: Hybrid proposals for context reasoning stand out in the literature, these proposals allow the use of two or more reasoning strategies. Motivated by this scenario, this paper aims to build the state of the art, systematizing research trends in Context Awareness. A Systematic Literature Review is explored, contributing to the identification of relevant works in the area, as well as the specification of criteria for its selection. In this review, we analyze works published between 2012 and 2017. During the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the literature, several papers explore hybrid strategies for context reasoning in IoT. To identify these papers, we performed a Systematic Literature Review (SLR) analyzing papers published between 2012 and 2017, more details can be found in [16]. SLR is a research methodology that foresees the execution of some procedures to generate a literature review in an area, to identify a set of papers that bring a precise prospection of the addressed state of the art [11].…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, several papers explore hybrid strategies for context reasoning in IoT. To identify these papers, we performed a Systematic Literature Review (SLR) analyzing papers published between 2012 and 2017, more details can be found in [16]. SLR is a research methodology that foresees the execution of some procedures to generate a literature review in an area, to identify a set of papers that bring a precise prospection of the addressed state of the art [11].…”
Section: Related Workmentioning
confidence: 99%